Pengaruh Respon IMF terkait Penggunaan Cryptocurrency terhadap Kebijakan Pemerintah Indonesia - Nugraha, Granitio Karya; Putranti, Ika Riswanti (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2018)
This research aims to describe the IMF response to cryptocurrency and its influence toIndonesian policy. The rapid development and the enormous potential of usingcryptocurrency to the world economy has triggered a diverse response from various partiesin the world. IMF, as an international institution that is engaged in economics, has so far afairly positive response related to the use of cryptocurrency in the world. This is due to thelarge potential possessed by cryptocurrency and the technologies that exist within it.However, so far there has been no policy issued by the IMF related to the use ofcryptocurrency. In contrast to the IMF, Indonesia, which is one of the member countries ofthe IMF has a different view and clearly prohibits the use of cryptocurrency as a mediumof exchange in Indonesia. Using the Regime Theory, Neoliberal Institutionalism, and theconcept of International Regime, this research attempts to explain what factors are behindthe IMF's support for the use of cryptocurrency. In addition, this research will also explainthe influence that the IMF has on its member states and try to predict how the IMF'sresponse to the use of cryptocurrency will affect future Indonesian government policy.Keywords:Â